TSG-6 promotes healing of critical-sized bone defects in mice - Küppers, Oliver; Ahmad, Mubashir; Dieterich, Sandra; Bülow, Jasmin Maria; Kölbl, Christoph; Haffner-Luntzer, Melanie; Scharffetter-Kochanek, Karin; Ignatius, Anita; Fischer, Verena (Frontiers in Immunology, 2025)
Tumor necrosis factor-stimulated gene 6 (TSG-6) is recognized for its anti-inflammatory and pro-regenerative properties in various inflammatory conditions, including peritonitis, arthritis, traumatic brain injury, and corneal as well as skin wound healing. However, its regenerative role in bone metabolism and repair remains largely unexplored. This study aimed to address this gap. We observed an increased expression of Tnfaip6 (Tsg-6) during early osteogenic differentiation of murine mesenchymal stem cells (mMSCs). Silencing Tnfaip6 significantly impaired osteogenic differentiation, as indicated by reduced alkaline phosphatase activity and downregulation of key osteogenic marker genes. RNA-seq analysis of Tnfaip6-deficient mMSCs revealed decreased expression of several genes that are critical for bone formation and healing, including matrix metallopeptidase 13, decorin, membrane metallopeptidase, and integrin binding sialoprotein. Conversely, gremlin 1, a known inhibitor of osteoblastogenesis, was significantly upregulated. To investigate the in vivo relevance, we assessed the effects of locally delivered recombinant TSG-6 (rTSG-6), embedded in a collagen gel, on bone regeneration in a 1.5 mm critical-sized femoral defect model in male C57BL/6J mice. Treatment with 50 μg rTSG-6 significantly enhanced bone formation compared to untreated and low-dose (10 µg) controls at 35 days post-injury. This effect was associated with increased osteoblast activity and reduced osteoclast activity. Moreover, rTSG-6 promoted M2 macrophage polarization and increased T-helper cell infiltration at the defect site three days after injury. In summary, TSG-6 enhances bone regeneration in critical-sized bone defects, through immunomodulation, particularly via M2 macrophage polarization, and stimulation of osteogenesis. These findings identify TSG-6 as a promising therapeutic candidate to improve bone repair, for example, in patients with osteoporosis, concomitant trauma or large bone defects.